Meningkatkan hasil belajar matematika melalui pendekatan pemecahan masalah pada siswa kelas V SD Negeri 2 Bone-Bone Kota Baubau pada pokok bahasan FPB dan KPK - Sardin Sardin; Rahmat Rajab (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2017)
The purpose of this classroom action research is to know about learning activity and to improve the learning result of class V student’s learning on GCD and LCM subject in SD Negeri 2 Bone-Bone through the application of the problem-solving approach. This research is carried out in the stages of planning, action, observation, and reflection. Instruments used in the form of Tests, to measure the level of achievement of learning outcomes conducted by students and observation sheets, to determine the increase in student and teacher activity. The target of learning mastery is 75%. The result data showed that the improvement of learning outcomes is reflected from the achievement of KKM in the initial test of 36%, increasing in the first cycle to 72%, and increasing in the second cycle to 88%. There is an increase in student activity from the first cycle of 65% (active enough) to 90% (very active) in the second cycle. There is an increase in teacher activity from the first cycle of 71.11% (good) to 93.33% (excellent) in the second cycle. Based on the results of the study concluded that the application of problem-solving approach in learning can improve student learning outcomes and activities of students and teachers in learning mathematics.